Metazoan parasites of rudd Scardinius erythrophthalmus in Lake Sapanca, Turkey - (:unkn) unknown (EUR ASSOC FISH PATHOLOGISTS, 2013)
In total 161 rudd (Scardinius erythrophthalmus) from Lake Sapanca (Turkey) were sampled between October 2009 and September 2010 and examined for the occurrence of metazoan parasites. Parasites were found in 152 (94.4%) individuals and 13 parasite species were recorded: Dactylogyrus difformis, D. difformoides, D. sphyrna and Paradiplozoon sp. (Monogenea); Posthodiplostomum cuticola metacercariae, Diplostomum sp. metacercariae, Tylodelphys clavata metacercariae and Clinostomum complanatum metacercariae (Digenea); Neoergasilus japonicus, Lamproglena pulchella and Argulus foliaceus (Crustacea); Piscicola geometra (Hirudinea); and glochidia larva (Mollusca). The most common species in the metazoan parasite community were D. difformis D. difformoides, L. pulchella and P. cuticola. Distinctive seasonal variation were observed for the prevalence and mean intensity of D. difformis D. difformoides, N. japonicus, P.cuticola, Diplostomum sp. and glochidia.
Keywords: NEOERGASILUS-JAPONICUS POECILOSTOMATOIDA; 1ST RECORD; COPEPOD; ERGASILIDAE; HARADA